Using perceived norms to predict heavy alcohol use among college students: implications for social norms marketing campaigns - Zaleski, Adam C., author; Aloise-Young, Patricia, advisor; Henry, Kim, committee member; Cross, Jennifer, committee member; Conner, Brad, committee member (Colorado State University. Libraries, 2015)
The purpose of the present study was to investigate the relationship between perceived norms of heavy peer alcohol use and self-reported heavy alcohol use among college students from a large public university. A total of 865 participants completed a survey in Fall 2008 and 506 of those participants completed the follow-up survey in Spring 2009. As hypothesized, the perceived injunctive norm was found to predict additional unique variance in heavy alcohol use above and beyond gender, year in school, residence hall, retrospective high school alcohol use and the perceived descriptive norm. The interaction between the perceived injunctive norm and perceived descriptive norm was not significant in the prediction of heavy alcohol use, as hypothesized. This suggests that the combined effect of the perceived injunctive norm and perceived descriptive norm in predicting heavy alcohol use is additive and not multiplicative. In a secondary hypothesis, the relationship between the perceived descriptive norm and heavy alcohol use was stronger for males than females. Lastly, as predicted, the results revealed that the relationship between perceived norms of heavy alcohol use and self-reported heavy alcohol use are stronger among more proximal than distal groups. These results suggest that social norms marketing campaigns aimed at reducing heavy alcohol use among college students should include the injunctive norm, target males, and use more proximal reference groups such as the student’s own residence hall rather than more distal reference groups such as the typical university student.
Keywords: descriptive norm; social influence; college alcohol use; social norms; injunctive norm